HUBUNGAN PENGETAHUAN PERAWAT DENGAN PENANGANAN KEJANG DEMAM PADA PASIEN ANAK DI RUMAH SAKIT SANTA ELISABETH BATAM KOTA TAHUN 2022 - Ernita Rante Rupang; Murni Simanullang; Juliana Erni Tamba (Jurnal Cakrawala Ilmiah, 2024)
Febrile seizure are one of the things that can affect the development of children in certain events especially in long-seizures (> 15 minutes) usually accompanied by apnea so that there is hypoxic occurrence of oxygen deficiency in the network. febrile seizure usually occurs in children aged 3-5 years. This is because at the age of the child's brain is very vulnerable to the increase in sudden body temperature. The top incident age around of 18 months and may disappear at the child of 8 years old. This study aims to determine the relationship of nurse knowledge with the treatment of fever seizures in children at the Santa Elisabeth Batam Hospital. This research uses cross-sectional design method, which is measurement or observation at the same time (one time) between risk factors / exposure with disease. The instrument used in this research is questionnaire. The questionnaire consisting of 12 questions. The results of this study named the nurse knowledge of febrile seizures in children at Elisabeth Batam hospital. the city were in a 27 good category (61.4%) and quite 17 respondents (38.6) and handling of fever seizures in children at Elisabeth Batam hospital were located in the contracts of both 26 respondents (59.71%) and adequaetly 18 respondents (40.9%) and there is a relationship nurse knowledge handling the febrile seizure at the Elisabeth Batam Hospital with result value of P-value 0.005. For further researchers, it is hoped that the results of this study can be used as a basis for developing further research such as other factors that influence febrile seizures.